Data analysis of the observation on spiders (Araneae) diversity in the Bulgarian part of Osogovo mauntain - Cholakova, Dema (Annual of Natural Sciences Department, 2024)
Osogovo Mountain occupies the largest part of the Osogovo-Belasitsa region and is located in its northernmost part. The highest point of the mountain is Mount Ruen (2251 m). In general, the Osogovo Mountain has an asymmetrical character: steep northern slopes, relatively sloping and separated by numerous ridges eastern and southwestern slopes, which is a prerequisite for the presence of rich biodiversity. The aim of this study is to establish the biodiversity (species composition) and more important biological, ecological and zoogeographical features of spiders (Araneae) from the Bulgarian part of the Osogovo Mountain.